Elective Affinity and the Domestication of Islamic Discourse in English Translation - Abdullah Saleh Aziz MOHAMMED (International Journal of Linguistics, Literature and Translation, 2025)
The translation of Quran provides access to the Word of Allah for non-Arabic speakers. This study explores the role of how elective affinities, a term made popular by Goethe and Max Weber, guide the translators’ choices in four translations of the Quran, i.e. George Sale (1734), Marmaduke Pickthall (1930), Abdullah Usuf Ali (1934) and M.A.S. Abdel Heleem (2004/2010). The study focuses on Surat Al-Baqara (Chapter 2), and draws on Lawrence Venuti’s domestication/foreignization dichotomy. Using elective affinities as an explanatory farmwork, the study adopts a close comparative, hermeneutic analysis of key Quranic concepts. The paper argues that translators’ lexical, stylistic and interpretive choices are not merely linguistic but reflect deep ideological, theological and cultural resonance between their worldviews and the dominant epistemic norms of the Anglophone target culture. The findings reveal four distinct domestication profiles: Sale’s Protestant-Orientalist domestication, Pickthall’s foreignized content in Biblical English aesthetics (stylistic domestication), Yusuf Ali’s universalist moralist domestication fed by early 20th century interfaith and Victorian ethics, and Abdel Haleem’s contemporary academic domestication that prioritises clarity and post-9/11 apologetic concerns. The findings also show that such domesticating tendencies can enhance readability and familiarity but they often entail semantic shifts and doctrinal flattening, and at times imply subordination of the Quranic concepts to target culture’s theological expectations. This study fills an underexplored gap in Translation studies, definitely unexplored in the translation of Quran. It offers a nuanced understanding of how ideological presuppositions give shape to the transmission and reception of sacred discourse in English.